GENETIKA FANINI O’QITISHDA QO’LLANILADIGAN ZAMONAVIY YONDASHUVLAR VA INNOVATSION TEXNOLOGIYALAR - Abdullayeva Gulzebo (TADQIQOTLAR, 2026)
Abstract: This article examines modern approaches and innovative technologies used in teaching genetics and their impact on improving educational effectiveness. The study highlights learner-centered teaching methods, digital technologies, interactive learning tools, virtual laboratories, and multimedia resources that contribute to enhancing students’ understanding of genetic concepts. Special attention is given to the integration of information and communication technologies, problem-based learning, and practical applications in genetics education. The findings suggest that the implementation of innovative educational strategies increases student engagement, develops analytical thinking skills, and improves the quality of genetics education. The article emphasizes the importance of adapting teaching methods to modern educational requirements and technological advancements.